Forecast of China’s Annual Carbon Emissions Based on Two-Stage Model - Zhang, Xiaolei; Xiong, Jingbo; Song, Jianqi (Frontiers in Environmental Science, 2022)
China’s carbon emissions are a major global concern. China has proposed a defined “dual-carbon” aim, with the first target being to attain the carbon emissions peak by 2,030. To address this issue, this study provides a two-stage method for forecasting China’s annual carbon emissions, which is paired with pertinent carbon emissions data to predict China’s annual carbon emissions. We discovered the associated aspects affecting China’s carbon emissions through the research of this article, and we predicted the carbon emissions data from 2017 to 2020 using the two-stage technique based on these factors. When compared to the actual data of China’s annual emissions from 2017 to 2020, the prediction intervals from this method encompass the actual data well. This method, on the one hand, identifies the main affecting factors for estimating carbon emissions data, and on the other hand, it validates the method’s performance. It provides support for further policy development and change based on the outcome of this method.